Flexibility transition and guest-driven reconstruction in a ferroelastic metal–organic framework. Issue 2 (14th October 2014) - Hunt, Sarah J.; Cliffe, Matthew J.; Hill, Joshua A.; Cairns, Andrew B.; Funnell, Nicholas P.; Goodwin, Andrew L.
Abstract : Copper(i ) tricyanomethanide shows exceptional mechanical and coordination flexibility in response to temperature and guest sorption. Abstract : The metal–organic framework copper(i ) tricyanomethanide, Cu(tcm), undergoes a ferroelastic transition on cooling below T f = 240 K. Thermal expansion measurements reveal an order-of-magnitude variation in framework flexibility across T f . The low-temperature phase α-Cu(tcm) exhibits colossal positive and negative thermal expansion that is the strongest ever reported for a framework material. On exposure to acetonitrile, Cu(tcm) undergoes a reconstructive solid-phase transition to acetonitrilocopper(i ) tricyanomethanide. This transition can be reversed by heating under vacuum. Infrared spectroscopy measurements are sensitive to the phase change, suggesting that Cu(tcm) may find application in solid-phase acetonitrile sensing.